2014
DOI: 10.2214/ajr.13.11692
|View full text |Cite
|
Sign up to set email alerts
|

MRI Findings After Prostatic Artery Embolization for Treatment of Benign Hyperplasia

Abstract: MRI can be used for assessing the development of infarcts and volume reduction in the prostate after embolization. Further studies are needed to correlate these findings to clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
2
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 37 publications
4
36
2
4
Order By: Relevance
“…Several subsequent studies showed variable degrees of mean prostatic volume reduction from 18% to 32% [8, 14, 19, 20]. In the present study, there was a significant mean reduction of 28.1 mL (31.4%) in total prostatic volume and 17.8 mL (29.9%) in transition zone prostatic volume after PAE.…”
Section: Discussionsupporting
confidence: 64%
“…Several subsequent studies showed variable degrees of mean prostatic volume reduction from 18% to 32% [8, 14, 19, 20]. In the present study, there was a significant mean reduction of 28.1 mL (31.4%) in total prostatic volume and 17.8 mL (29.9%) in transition zone prostatic volume after PAE.…”
Section: Discussionsupporting
confidence: 64%
“…Frenk et al 8 reported that infarct areas were found in 70% of their series of 17 patients treated with PAE; nevertheless, 100% clinical success was achieved.…”
Section: Discussionmentioning
confidence: 96%
“…8,14 In analysing preembolisation MRI studies, many differences among prostates, in addition to their size, shape, or symmetry, have been described. 15,16 On T2-weighted MRI, different patterns of signal intensity can be observed, and these are certainly related to prostate tissue composition.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a cavity after thermal ablation is of clinical implication because of its positive correlation with an improvement in urinary performance and relief of outlet obstruction (40). In our previous studies with PAE in a DeKlerk’s model, various sizes of intraprostatic cavities were observed in all beagles 1 month after embolization (31); whereas it rarely occurred and was observed in only one out of eleven patients with BPH after prostatic artery embolization (41). Interestingly, our findings were inconsistent with a similar animal experiment by Brook et al (42).…”
Section: Hormone-induced Bph Modelsmentioning
confidence: 94%